Myoepithelioma of the Parotid Gland: A Case Report with Review of the Literature and Classic Histopathology - Mark Weitzel; Jason E. Cohn; Harvey Spector (Case Reports in Otolaryngology)
Myoepithelioma is a rare salivary gland neoplasm. They most commonly affect the major and minor salivary glands with the parotid gland being the most common, approximately 40%. Only 1% of all salivary gland neoplasms are myoepitheliomas. Myoepithelioma is usually a benign tumor arising from neoplastic myoepithelial or basket cells which are found between the basement membrane and the basal plasma membrane of acinar cells. They also contain multiple cellular elements. We present a case of a 73-year-old female with myoepithelioma of the parotid gland, an extremely rare neoplasm. There have been approximately 42 cases reported through 1985 and fewer than 100 cases through 1993. We will discuss the clinical presentation, pathophysiology, diagnosis, and treatment of such neoplasms.